Cloning and characterization of Aedes aegypti juvenile hormone epoxide hydrolases (JHEHs). Issue 1 (18th October 2022) - Borovsky, Dov; Van Ekert, Evelien; Buytaert, Esther; Peeters, Tom; Rougé, Pierre
Abstract: Juvenile hormone epoxide hydrolase (JHEH) plays an important role in the metabolism of juvenile hormone III (JH III) in insects. To study the role that JHEH plays in female Aedes aegypti JHEH 1, 2, and 3 complementary DNA (cDNAs) were cloned and sequenced. Northern blot analyses show that the three transcripts are expressed in the head thorax, the gut, the ovaries, and the fat body of females. Molecular modeling shows that the enzyme is a homodimer that binds JH III acid (JH IIIA) at the catalytic groove better than JH III. The cDNA of JHEH 1 and 2 are very similar indicating close relationship. Knocking down of jheh 1, 2, and 3 in adult female and larval Ae. aegypti using double‐stranded RNA (dsRNA) did not affect egg development or caused adult mortality. Larvae that were fed bacterial cells expressing dsRNA against jheh 1, 2, and 3 grew normally. Treating blood‐fed female Ae. aegypti with [12‐ 3 H](10R) JH III and analyzing the metabolites by C18 reversed phase chromatography showed that JHEH preferred substrate is not JH III but JH IIIA. Genomic analysis of jheh 1, 2, and 3 indicate that jheh 1 and 2 are transcribed from a 1.53 kb DNA whereas jheh 3 is transcribed from a 10.9 kb DNA. All three genes are found on chromosome two at distinct locations. JHEH 2 was expressed in bacterial cells and purified by Ni affinity chromatography. Sequencing of the recombinant protein by MS/MS identified JHEH 2 as the expressed recombinant protein. Abstract : Juvenile hormone III (JH III) is first metabolized into JH III acid by JH III esterase and then into JH III acid diol by JH epoxide hydrolase (JHEH. JH III is not a good substrate for JHEH whereas JH III acid is. This was shown by in vivo and 3D molecular modeling studies. Research highlights: The role of juvenile hormone epoxide hydrolases 1, 2, and 3 (JHEHs) in Aedes aegypti was investigated. The enzymes are expressed ubiquitously in the gut, head thorax region and the ovary of female Ae. aegypti . Using in vivo and 3D modeling we showed that JHEH prefers to metabolize Juvenile hormone (JH) acid into JH acid diol rather then JH into JH diol. These results indicate that JH esterase has the primary role and JHEH has a secondary role in JH III metabolism in Ae. aegypti .